A late Miocene–early Pliocene baleen whale assemblage from Langebaanweg, west coast of South Africa (Mammalia, Cetacea, Mysticeti). Issue 4 (1st October 2016) - Govender, Romala; Bisconti, Michelangelo; Chinsamy, Anusuya
Abstract : Govender, R., Bisconti, M. & Chinsamy, A., June 2016. A late Miocene–early Pliocene baleen whale assemblage from Langebaanweg, west coast of South Africa (Mammalia, Cetacea, Mysticeti). Alcheringa 40, xxx–xxx. ISSN 0311-5518 Knowledge of post-Eocene cetaceans from Africa is very poor with almost nothing known about this group from southern Africa except for the diverse trawled ziphiids. Langebaanweg, a locality yielding prolific Miocene–Pliocene fossils on the southwestern Cape coast of South Africa, preserves terrestrial and marine biotas in juxtaposition. Palaeoenvironments vary from a marine shoreline to a lagoon and estuary and later a shallow marine environment and include several microhabitats. Fragmentary preservation of the cetacean skeletons suggests that they were transported before burial. This first detailed analysis of the Mio-Pliocene mysticete fossils from Langebaanweg uses the petrotympanic region to taxonomically identify specimens. Three un-named species of balaenopterid Mysticeti represent a Plesiobalaenoptera -like form, but it is premature to erect a new taxon based on this fragmentary material. The remaining material is too poorly preserved to be identified with confidence. Romala Govender [ rgovender@iziko.org.za ], Natural History Department, Iziko Museums of South Africa, PO Box 61, Cape Town, 8001, South Africa; Biological Sciences, University of Cape Town, Private Bag X3, Rhodes Gift, 7701, Cape Town, South Africa, Michelangelo Bisconti [ michelangelobisconti@gmail.com ], Natural History Museum of San Diego, California, 1788 El Prado, San Diego, CA 92101, USA; Anusuya Chinsamy [ anusuya.chinsamy-turan@uct.ac.za ], Biological Sciences, University of Cape Town, Private Bag X3, Rhodes Gift, 7701, Cape Town, South Africa.